2003
DOI: 10.1002/ps.762
|View full text |Cite
|
Sign up to set email alerts
|

The ability of indigenous micro‐organisms to degrade isoproturon, atrazine and mecoprop within aerobic UK aquifer systems

Abstract: The potential for the herbicides isoproturon, atrazine and mecoprop to degrade in the major UK aquifers of chalk, sandstone and limestone was studied using laboratory microcosms spiked at 100 microg litre(-1). Significant mecoprop degradation was only observed in sandstone groundwater samples. Atrazine transformation, based on the formation of metabolites, did occur in most groundwater samples, but only at a rate of 1-3% per year. A potential to degrade isoproturon was observed in groundwater samples from each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…In previous studies of the fate of isoproturon in groundwaters we demonstrated that its rate of degradation varied considerably, both spatially and temporally [6,7]. An aim of this study was to determine the microbial basis of this observed variation and in particularly the possible correlation with microbial community composition, abundance and groundwater chemistry.…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies of the fate of isoproturon in groundwaters we demonstrated that its rate of degradation varied considerably, both spatially and temporally [6,7]. An aim of this study was to determine the microbial basis of this observed variation and in particularly the possible correlation with microbial community composition, abundance and groundwater chemistry.…”
Section: Discussionmentioning
confidence: 95%
“…Yet degradation was reported in sandy aquifers (half-lives (T 1/2 ) up to 3.6 years), in groundwater from rock aquifers (T 1/2 0.09-2 years), and even mineralization in aquifer chalk (T 1/2 of 11-12 years) (Johnson et al, 2000(Johnson et al, , 2003Kristensen et al, 2001;Mouvet et al, 2004). However, slow mineralization in sandy aquifer sediment was recently and apparently for the first time reported with just 3% mineralized in 8 months (Janniche et al, 2010a).…”
Section: Mineralization Abilitymentioning
confidence: 93%
“…Atrazine degradation (as removal of the parent compound) but not mineralization has previously been reported in groundwater samples with half-lives of 50-100 years (Johnson et al, 2000(Johnson et al, , 2003, and in sandy aquifer sediment when incubated with extremely high concentrations (4.5 mg/L) (McMahon et al, 1992). In most studies though, atrazine was recalcitrant and not degraded e.g.…”
Section: Mineralization Abilitymentioning
confidence: 93%
“…Most researchers conclude that both chemical and microbial dissipation of atrazine in soil is important (Johnson et al, 2003;Sirons et al, 1973). Half-life estimates for atrazine range from 21 to 80 days (Winkelmann and Klaine, 1991;Smith and Walker, 1989); although Jones et al (1982) determined the half-life to be 330 and 385 days in two agricultural soils.…”
Section: Introductionmentioning
confidence: 96%